2018
DOI: 10.3892/ijmm.2018.3672
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β‑mediated Ser156 phosphorylation modulates a BH3‑like domain in BCL2L12 during TMZ‑induced apoptosis and autophagy in glioma cells

Abstract: BH3 domains, classified initially as BCL2 homology domains, participate in both apoptosis and autophagy. Beclin-1 contains a BH3 domain, which is required for binding to antiapoptotic BCL2 homologs and BCL2-mediated inhibition of autophagy. BCL2-like 12 (BCL2L12) also harbors a BH3-like domain, which is 12 residues long and contains a LXXXAE/D motif. In a yeast two-hybrid system performed in the present study, BCL2L12 shared similar binding partnerships to antiapoptotic BCL2 homologs, such as Beclin-1. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Beclin-1 interacts with several binding partners and can both induce and suppress autophagy pathways [23]. While numerous commonly used anticancer drugs have been reported to induce apoptosis in cancer cells, autophagy was also frequently observed in response to these drugs, including THD, TMZ, ABT-737, and sorafenib [3,4,21,24,25]. In our previous study, we found that THD and its analogs might enhance LC3-II-induced autophagy in GBM cells (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beclin-1 interacts with several binding partners and can both induce and suppress autophagy pathways [23]. While numerous commonly used anticancer drugs have been reported to induce apoptosis in cancer cells, autophagy was also frequently observed in response to these drugs, including THD, TMZ, ABT-737, and sorafenib [3,4,21,24,25]. In our previous study, we found that THD and its analogs might enhance LC3-II-induced autophagy in GBM cells (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, AMPK activation was involved in THD-induced autophagy [21]. Studies have revealed that treatment with ABT-737 (a BH3 mimetic agent) combined with TMZ exerted a superior effect on apoptosis induction in U87MG cells, which effectively reactivated apoptotic markers [3,4]. Thus, to investigate the effect of a combination of THD and TMZ, U87MG cells were treated with different doses of THD combined with 200 µM TMZ for 24 h. As illustrated in Figure 3C, the level of phospho-AMPK (Thr172) was upregulated in the U87MG cells after the combination treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Published data indicate that Bcl2L12 is an anti‐apoptotic molecule . To elucidate if Bcl2L12 is involved in the regulation of FasL expression, the expression of Bcl2L12 in peripheral CD4 + T cells were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Allen et al reported the origin of the U-87 MG cell line as mislabeled and unknown; they compared the original U-87MG cell line firstly identified at Uppsala University with the commercial U-87MG cell line from ATCC HTB 14TM. Genotyping analysis revealed that the ATCC and Uppsala U-87 MG cell lines were from distinct origins [ 57 ]; however, other recent studies [ 58 , 59 , 60 ] have demonstrated that the U-87MG ATCC cell line has several typical characteristics of glioblastoma through analyses of cell morphology and gene expression profile, even though the origin patient is unknown. Thus, U-87 MG can be used as a bonafide human glioblastoma cell line.…”
Section: Methodsmentioning
confidence: 99%